Utility of Coil-Assisted Retrograde Transvenous Obliteration II (CARTO-II) for the Treatment of Gastric Varices - Yamamoto, Akira (Cardiovasc Intervent Radiol, 2019)
PURPOSE: To investigate the technical feasibility, safety and clinical outcomes of coil-assisted retrograde transvenous obliteration II (CARTO-II) for gastric varices (GV). MATERIALS AND METHODS: Thirty-six consecutive patients who had undergone CARTO-II between June 2016 and April 2018 were included in the study. In the CARTO procedure, coil embolization of the drainage vein is performed “before” injection of the sclerosant to replace the use of balloon catheter. In the CARTO-II procedure, coil embolization of the drainage vein was performed “after” injection of the sclerosant to prevent migration of the sclerosant. CARTO-II was performed with ethanolamine oleate iopamidol, and the balloon catheter was immediately removed after coil placement. Technical and clinical success rates, number of coils used, presence or absence of severe complications, timing of the procedure, and rate of GV recurrence after the procedure were analyzed retrospectively. RESULTS: In all patients, GV sclerosis, coil placement and removal of the balloon catheter were successfully completed. The technical success rate was 100%. No patients experienced severe complications such as coil migration or pulmonary embolization. The mean number of metallic coils used per procedure was 3.36. Mean length of the procedure was 132.8 min. Contrast-enhanced computed tomography after CARTO-II confirmed complete variceal thrombosis in all cases. The recurrence rate of GV during follow-up was 2.8% (mean follow-up, 207 days). CONCLUSION: CARTO-II was feasible and safe and could be performed relatively quickly. The number of coils used and the rate of GV recurrence were both low. CARTO-II may have an important role to play in the management of GV.